2019
DOI: 10.1021/acs.joc.8b02973
|View full text |Cite
|
Sign up to set email alerts
|

Substituent Effects on 3-Arylazoindole Photoswitches

Abstract: The development and investigation of heteroazo switches has flourished in recent years. Because of their specific photophysical and photochemical properties, they find versatile applications from material science to medicine. However, a deep mechanistic understanding is needed to be able to predict the properties of such azoswitches. In particular, the effect of different substituents on the azo chromophore is of great interest as they are often crucial for embedding the molecular switch into a system of inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…section 6 in the ESI). 63 The spectra of naphthyridine methylcarbamate and the azobenzene core structure in NCDA3 are depicted in Figure 3 (black and red solid lines, respectively). The first allowed transition of the naphthyridine methylcarbamate at 294 nm overlaps substantially with the main band of E-CH2NHCH3, namely its ππ* transition, at 355 nm.…”
Section: Resultsmentioning
confidence: 99%
“…section 6 in the ESI). 63 The spectra of naphthyridine methylcarbamate and the azobenzene core structure in NCDA3 are depicted in Figure 3 (black and red solid lines, respectively). The first allowed transition of the naphthyridine methylcarbamate at 294 nm overlaps substantially with the main band of E-CH2NHCH3, namely its ππ* transition, at 355 nm.…”
Section: Resultsmentioning
confidence: 99%
“…This result is disappointing, because the photoswitchable sirtuin inhibitor 11 cannot be switched between active and inactive state, as envisioned. Possible reasons could be assigned to substituent effects as demonstrated by Simeth et al [62]. As recently reported by Schehr et al, reducing agents like DTT, used to prevent enzyme oxidation in crystallization mixtures or in vitro assays, can reduce azo dyes to hydrazine derivatives very fast and thus disable photoisomerization [63].…”
Section: Discussionmentioning
confidence: 99%
“…That is why this reaction should be controlled, which can be done to some extent, through the introduction of adequate substituents. 29 , 30 In one of our previous works, we have shown that the geometry of the electron-donating group determines its donating character and the photoisomerization rate constant, 29 yet it remains unknown (i) if the photoisomerization is dependent on such subtle structural changes as the ones studied herein and (ii) if changing the position of one nitrogen atom only allows the tuning of the fluorescence quantum yields. For the former aspect, let us mention that the photoisomerization of the double N=N bond in phenylazadiazines might indeed be influenced by the position of the nitrogen atom.…”
mentioning
confidence: 90%
“…While the elongated π-conjugation path between the electron-donating and electron-accepting moieties is beneficial for maximizing two-photon absorption cross section, the presence of an alkenyl moiety may lead to trans – cis photoisomerization. 22 28 Although the photoisomerization might be desired in photochromic applications, it competes with fluorescence and is thus detrimental for our purposes. That is why this reaction should be controlled, which can be done to some extent, through the introduction of adequate substituents.…”
mentioning
confidence: 99%